Severe floods increase long-term opioid overdose mortality - Kristina Brant; Mengjun Ge; Zhen Lei (Proceedings of the National Academy of Sciences, 2026)
The relationship between climate disasters and substance use-related harms has been understudied. This study employed a mixed methods research design to assess the impact of severe floods on opioid overdose mortality and identify mechanisms driving this relationship. Drawing on opioid overdose death data from NCHS, presidential disaster declarations from FEMA, and severe storm event data from NOAA, we found severe floods in rural Appalachia led to a significant increase in county-level overdose mortality that persisted for a decade postflood. We then collected retrospective qualitative data from 17 stakeholders regarding the floods that occurred in Eastern Kentucky in July 2022. Interviews suggested this increase in overdose mortality was perpetuated by decreased access to treatment, recovery, and harm reduction services; increased trauma; increased instability; and persistent stigma around help-seeking. Due to the predicted continuation of these disasters, understanding their impact on substance use-related harms is essential to mitigating future damage.